A multiple perspective code of ethics framework for health care professionals in Malaysian public paperless hospitals [electronic resource] - Sapiah Sulaiman, 1979-; Rose Alinda Alias, supervisor; Azizah Abdul Rahman, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2008